(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
The alignment of employee competencies with job placement remains a critical issue in human resource management, particularly within healthcare organisations where service quality depends on workforce performance. This study investigates the effects of competence and job placement on employee performance, as well as the mediating role of job satisfaction in these relationships at the South Amuntai Community Health Centre, North Hulu Sungai Regency, Indonesia. A quantitative explanatory research design was employed, involving all 82 employees of the health centre, including civil servants, contract staff, and voluntary workers, through a saturated sampling technique. Data were collected using a structured questionnaire and analysed using Partial Least Squares Structural Equation Modelling with SmartPLS 4. The findings reveal that both competence and job placement exert positive and significant effects on employee performance. Job placement also demonstrates a positive and significant influence on job satisfaction, whereas competence does not significantly affect job satisfaction. In addition, job satisfaction significantly enhances employee performance. The mediation analysis indicates that job satisfaction does not mediate the relationship between competence and employee performance. However, it partially mediates the relationship between job placement and employee performance. These findings suggest that improving employee performance in primary healthcare institutions requires not only competent personnel but also appropriate job placement practices that foster higher job satisfaction. This study contributes to the public sector human resource management literature by providing empirical evidence of the mediating role of job satisfaction in linking job placement and employee performance within the context of primary healthcare services in Indonesia. Keywords: competence; job placement; job satisfaction; employee performance; primary healthcare;